Teacher curriculum-awareness and students' achievement in english oracy skills in Ibadan, Nigeria (2018)
This study investigated English language teacher curriculum awareness at senior secondary schools in Ibadan, Nigeria. The descriptive design was adopted for the study. The population of the study comprised all Senior Secondary English Language teachers and students in senior secondary schools in Ibadan, Nigeria. Simple random sampling was used to select six local government areas in Ibadan. Three public secondary schools were randomly selected from each local government area making a total of 18 schools, while purposive random sampling method was used to select three English language teachers and 50 students from each school making a total of 54 teachers and 900 students. The instruments used were: Teacher Curriculum Awareness Questionnaire (r=0.93) and Teachers Oral interview Guide for teachers on curriculum awareness (r=0,87). Descriptive statistics of frequency counts, mean and standard deviation were used in analyzing the quantitative data generated from the questionnaire, while qualitative data from oral interview were content-analysed. Results revealed that 63.3 7% of the teachers (mean=2.67) are aware of the English Language curriculum on oracy skill and their awareness is high. It is recommended that curriculum planners and designers should endeavor to make the copies of the English language curriculum available because it is one thing to plan and design the curriculum it is another thing for the curriculum to be readily available for the teachers.